The role played by Singlish in the lives of migrants in Singapore - You, Jing (2015)
The issue of migration has become a widely discussed topic recently. While migrants can help with economic growth of a country, their large presence may result in issues like xenophobia. To ease such tensions, integration is essential and this thesis investigates the role of Singlish, its usage and function in particular, in the lives of migrants in Singapore. The attitudes of these migrants towards Singlish was also assessed. 100 migrants took part in this quantitative study. No strong correlation was found between length of stay and the role of Singlish, in particular the usage, function and attitudes towards this variety. Instead, a strong correlation was found between long term goal of migration and role of Singlish. This shows that having an intention to stay in the country could affect the usage and function of Singlish, and attitudes towards this colloquial variety greatly. This thesis hence suggests that Singlish can be used both as a tool for identity construction and as a communication tool for migrants trying to integrate into Singapore.